Pendidikan Agama Islam Nonformal Sebagai Benteng Pertahanan Keimanan Anak di Pengajian Darunnajah Cimahi - Sonia, Gina; Drajat, Manpan (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
This study investigates the implementation of non-formal Islamic education at Pengajian Darunnajah Cimahi in response to concerns over children spending excessive time on gadgets and engaging in potentially harmful activities such as free mingling. It emphasizes the importance of instilling religious values from the most miniature community environments as a defense mechanism to strengthen individual faith. Using qualitative research methods, including in-depth interviews and participatory observations of educators and participants, the study explores how Pengajian Darunnajah Cimahi effectively integrates religious teachings to counteract the distractions of modern digital lifestyles and the risks associated with moral laxity. Findings underscore the program's role in fostering spiritual awareness and cultivating Islamic principles among youth. Despite sustainability challenges and educational delivery quality, the program positively reinforces religious identity and moral resilience among participants. Recommendations highlight the necessity for ongoing support to enhance non-formal Islamic education as an integral component of community-based initiatives.